DETERMINAN UKURAN PERUSAHAAN DAN OPINI AUDIT TERHADAP AUDIT DELAY - Dewi Anggraeni; Nur Aisyah; Hasbiah; Fitri (POLITEKNIK LP3I JAKARTA, 2024)
In the Financial Services Authority (OJK) Regulation number 44/POJK.04/2016 all issuers listed on the Indonesia Stock Exchange (IDX) are required to submit their annual financial reports no later than 3 (three) months or 90 (ninety days). Internal factors that affect audit delay are company size while external factors are audit opinions. This study was conducted using a quantitative approach with multiple linear regression methods. The data used are the annual reports of wholesale trading companies listed on the Indonesia Stock Exchange for 2019-2022. In addition, with the purposive sampling technique, issuers must submit their financial reports consecutively during the 2019-2022 period so that only 128 samples meet the requirements. The results show that company size and audit opinion partially have an effect on audit delay. The results of this study confirm that audit opinions have a negative effect on audit delay because the increasing number of unqualified opinions will reduce the number of days of the audit examination process. An issuer that receives an unqualified opinion means that it has met the financial report requirements according to accounting standards and has complied with the rules set for the company. This is also good news for management to immediately submit its audited financial report to interested parties